Pengaruh Kesadaran Wajib Pajak, Sanksi Pajak, Tingkat Pendidikan Terhadap Kepatuhan Wajib Pajak : ( Studi Kasus Pada Orang Pribadi Di KPP Pratama Depok Sawangan ) - Putri, Dema Okta; Nadi, Luh (Politeknik Negeri Ambon, 2024)
This research aims to provide empirical evidence that tax payer awareness, tax sanctions, and level of education affect taxpayer compliance among individuals at KPP Pratama Depok Sawangan. In this research, 2 variables are used, namely independent and dependent, where taxpayer compliance is the dependent variable while taxpayer awareness, tax sanctions and level of education are the independent variables. The simple random sampling method is the determination of the sample carried out in this research, where 100 respondent data was obtained as a result of distributing questionnaires. The data used is descriptive quantitative. Data analysis uses descriptive statistical testing, and hypothesis testing uses SPSS software. In this research, it was concluded that tax sanctions, taxpayer awareness, and education level were simultaneously able to influence taxpayer compliance. Furthermore, the taxpayer awareness variable is able to influence taxpayer compliance. The tax sanctions variable is unable to influence taxpayer compliance. The education level variable is unable to influence taxpayer compliance.